Video Animasi Sparkol sebagai Media Pembelajaran Literasi dan Numerasi Sekolah Dasar Muhammadiyah 24 Surabaya: Animated Video Sparkol As A Medium for Learning Literacy and Numeracy at Muhammadiyah 24 Primary School Surabaya - Budinan, Agus; Wahyuni, Holy Ichda (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Indonesia is one of the countries with a low level of literacy and numeracy skills. The Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) continues to strive to realize a culture of literacy and numeracy and encourage Indonesian people to be able to improve literacy and numeracy skills. Literacy and numeracy are very important skills that are built early and practiced from an early age so that they like literacy and make children a fun habit. The method used in research is a qualitative approach, because researchers want to explore the development, application, and impact of learning media. The research took place at SD Muhammadiyah 24 Surabaya. In data collection researchers use observation, interviews and documentation. Researchers use triangulation techniques to check the validity of the data in this study and activities in data analysis, namely data reduction, data display, and conclusion drawing/verification. This research is expected to contribute to the development of skills in facing 21st century education in the digital era, as well as produce scientific work that contributes to the development of science and technology.